MR imaging in radiation myelopathy. - Wang, P Y; Shen, W C; Jan, J S (American Journal of Neuroradiology, 1992)
PURPOSE Using MR imaging, we assessed the signal, size, and enhancing characteristics of the cervical cord in patients in whom radiation myelopathy developed after radiotherapy for nasopharyngeal carcinoma.PATIENTS AND METHODS Ten patients, 3 men and 7 women, aged from 32 to 77 years, were included. MR imaging was performed 1 to 53 months after clinical manifestations of myelopathy.RESULTS Two cases showed atrophy of the cervical cord without abnormal signal intensity; in the others, a long segment of the cervical cord demonstrated low signal intensity on T1-weighted images and high signal intensity on T2- or T2*-weighted images. Some of these cases also showed swelling of the cord. Focal enhancement at C1-C2 area after intravenous administration of Gd-DTPA was seen in four cases.CONCLUSIONS There is a correlation between the time of MR imaging after onset of symptoms and MR findings. When MR scans were obtained more than 3 years after onset of symptoms, atrophy of the cervical cord was noted without abnormal signal intensity. When MR was performed less than 8 months after onset of symptoms, a long segment of the cervical cord demonstrated abnormal signal intensity with or without associated swelling of the cord and focal enhancement.